If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -30 + -7a = 5a + 6(a + -8) Reorder the terms: -30 + -7a = 5a + 6(-8 + a) -30 + -7a = 5a + (-8 * 6 + a * 6) -30 + -7a = 5a + (-48 + 6a) Reorder the terms: -30 + -7a = -48 + 5a + 6a Combine like terms: 5a + 6a = 11a -30 + -7a = -48 + 11a Solving -30 + -7a = -48 + 11a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-11a' to each side of the equation. -30 + -7a + -11a = -48 + 11a + -11a Combine like terms: -7a + -11a = -18a -30 + -18a = -48 + 11a + -11a Combine like terms: 11a + -11a = 0 -30 + -18a = -48 + 0 -30 + -18a = -48 Add '30' to each side of the equation. -30 + 30 + -18a = -48 + 30 Combine like terms: -30 + 30 = 0 0 + -18a = -48 + 30 -18a = -48 + 30 Combine like terms: -48 + 30 = -18 -18a = -18 Divide each side by '-18'. a = 1 Simplifying a = 1
| 20-ln(5-x)=0 | | 8v+5(4+8v)=-23+5v | | 3x^2=144-x^2 | | 4b-8(4b-3)=-2-2b | | 4n-23=-8+7n | | 5(7x-8)-4x=-6x-3 | | 3z-12=12+7z | | 34-8x=2x-8(-2+2x) | | 40-8n=-8(1+4n) | | =s^3+4s^2+6 | | 8+5(6-3p)=-16-6p | | 6(-3x+1)-5x=-39-8x | | 10(3x+1+2)=34 | | 2*1r=4 | | 2x^2-40x-144=0 | | 6(5+x)-4x=24+5x | | 36-3m=-5(2m-3) | | -2n-8(-3n+4)=40+4n | | -n+3=-7(n+3) | | Tnr=pv | | 5x+3x+2x=3x+1 | | ax-c=borx | | 22+r=-(6-8r) | | 1-10y=27-3y+6 | | 5x-100+2x-25=75 | | 2x(3+y)=12 | | -20+4a=8(6-8a) | | 6(3+4x)-4=158 | | -(8x+8)-5=-8-3x | | -4n-21=-(-6-n)-2 | | 4x^2+3x+0=0 | | 81y^2-8=13 |